Evaluation of larvicidal potential against larvae of Aedes aegypti (Linnaeus, 1762) and of the antimicrobial activity of essential oil obtained from the leaves of Origanum majorana L. - Chaves, Renata do Socorro Barbosa (PLoS One, 2020)
This study evaluated the larvicidal activity of Origanum majorana Linnaeus essential oil, identified the chemical composition, evaluated the antimicrobial, cytotoxic and antioxidant potential. The larvicidal activity was evaluated against larvae of the third stage of Aedes aegypti Linaeus, whereas the chemical composition was identified by gas chromatography coupled to mass spectrometer, the antimicrobial activity was carried out against the bacteria Pseudomonas aeruginosa, Escherichia coli and Staphylococcus auereus, the antioxidant activity was evaluated from of 2.2-diphenyl-1-picryl-hydrazila sequestration and Artemia salina Leach cytotoxicity. Regarding to the results, the larvicidal activity showed that O. majorana L. essential oil caused high mortality in A. aegypti L. larvae. In the chromatographic analysis, the main component found in O. majorana L. essential oil was pulegone (57.05%), followed by the other components verbenone (16.92%), trans-p-menthan-2-one (8.57%), iso-menthone (5.58%), piperitone (2.83%), 3-octanol (2.35%) and isopulegol (1.47%). The antimicrobial activity showed that E. coli and P. aeruginosa bacteria were more sensitive to oil than S. aureus, which was resistant at all concentrations. Essential oil did not present antioxidant activity, but it has high cytotoxic activity against A. salina L.